![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
⇔(2 x ) 2+2.2 x .1+1 2=0 ... c ,(3 x −4) 2−14(3 x −4)(6+3 x )+49(3 x +6)=16 ... ⇔9 x 2−24 x +16−126 x 2−252 x +168 x +336+147 x +294=16.
https://olm.vn/hoi-dap/detail/192758180810.html
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
\(-\left(4x-1\right)-\left(5x+1\right)-\left(1-3x\right)=4\left(2x-1\right)+6\\ \Leftrightarrow-4x+1-5x-1-1+3x=8x-4+6\\ \Leftrightarrow-6x-1=8x+2\\ \Leftrightarrow-6x-8x=2+1\\ \Leftrightarrow-14x=3\\ \Leftrightarrow x=-\dfrac{3}{14}\)
Vậy \(x=-\dfrac{3}{14}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(3x-15\right)\left(2x-6\right)=2x-6\)
\(\Leftrightarrow\left(3x-15\right)\left(2x-6\right)-\left(2x-6\right)=0\)
\(\Leftrightarrow\left(2x-6\right)\left(3x-16\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x-6=0\\3x-16=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=\frac{16}{3}\end{cases}}\)
(3x-15).(2x-6)=2x-6
3x-15 =(2x-6):(2x-6)
3x-15 =1
3x =1+15
3x =16
x =16:3
x = 8
Vậy x =8
![](https://rs.olm.vn/images/avt/0.png?1311)
1) (3x + 9)(3x - 6) = 0
=> \(\orbr{\begin{cases}3x+9=0\\3x-6=0\end{cases}}\)
=> \(\orbr{\begin{cases}3x=-9\\3x=6\end{cases}}\)
=> \(\orbr{\begin{cases}x=-3\\x=2\end{cases}}\)
Vậy ...
b) (2x + 15) - 25 = 47 - (10 - x)
=> 2x - 10 = 37 + x
=> 2x - x = 37 + 10
=> x = 47
3, tương tự
4) |4 - 3x| = 8
=> \(\orbr{\begin{cases}4-3x=8\\4-3x=-8\end{cases}}\)
=> \(\orbr{\begin{cases}3x=-4\\3x=12\end{cases}}\)
=> \(\orbr{\begin{cases}x=-\frac{4}{3}\\x=4\end{cases}}\)
Vì x là số nguyên nên ...
còn lại tương tự
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 12+(2x-11)=53
(2x-11) = 53-12
2x-11= 41
2x=41+11
2x=52
x= 52:2
x=26
Vậy...
\(b,21-\left(-6+3x\right)=9\)
\(\Rightarrow21+6-3x=9\)
\(\Rightarrow27-3x=9\)
\(\Rightarrow3x=18\)
\(\Rightarrow x=6\)
c, -(2x+4)+11=-27
=>-2x-4+11=-27
=>-2x+7=-27
=>-2x = -34
=>x=17
d, 33-(33-x)=0
=>33-33+x=0
=>x=0
4 - 3x = 2x - 6
=> 4 + 6 = 2x + 3x
=> 10 = 5x
=> x = 2
Vậy .....
4 - 3x = 2x - 6
4 - 3x - 2x +6 = 0
-5x + 10 = 0
-5 ( x - 2 ) = 0
x- 2 = 0
x = 2